A new species of Uroplatus (Gekkonidae) from Ankarana National Park, Madagascar, of remarkably high genetic divergence - Ratsoavina, Fanomezana M.; Scherz, Mark D.; Tolley, Krystal A.; Raselimanana, Achille P.; Glaw, Frank; Vences, Miguel (Zootaxa, 2019)
Previous studies on leaf-tailed geckos of the genus Uroplatus identified a lineage from the Ankarana karst massif in northern Madagascar as genetically highly divergent, but only fragmentary information was available on these geckos. Here, we provide an integrative analysis based on molecular and morphological data, including a newly collected specimen from this locality. Phylogenetic analysis placed the Ankarana lineage sister to U. ebenaui, but with a surprisingly high genetic divergence of over 19% uncorrected pairwise distance in the mitochondrial 16S rRNA gene. We formally describe the Ankarana lineage as Uroplatus fetsy sp. nov. and provide new information on the distribution and genetic differentiation of its sister species, Uroplatus ebenaui. Based on DNA sequences of newly examined samples this latter species is confirmed as widespread, ranging from low-elevation dry forests from Beanka in western Madagascar to Forêt d’Ambre and Analalava/Fanambana in northern Madagascar, and thus far has not been found in the Ankarana Massif, where U. fetsy occurs.